Motion Graphic Rate Card TVC Batam TV - Nur Imma Aulia Astori; Sandi Prasetyaningsih (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2021)
PT. Batam Multimedia Television (Batam TV) is a local television station established on January 17, 2003 and Batam TV is included in the Jawa Pos Multimedia Group (JPM) as the first local television station in the Riau Islands. The implementation of Motion Graphic Rate Card TVC Batam TV, aims to provide attractive packaging information to the public regarding the price rates for advertising on Batam TV. The information that will be conveyed includes all price rates starting from day, hour and time.The motion graphics in this promotional video are created using the product development and validation method, Villamil - Molina. After the product is finished, the next step is to analyze the level of influence and effectiveness of the promotion media in the form of motion graphics using the EPIC Model.The results of the analysis use the EPIC Model parameters, namely the Empathy, Persuation, Impact and Communocation dimensions. It is hoped that this motion graphic can convey information clearly, easily understood and at the same time help the public, especially Batam, get information about the pricing rates for advertising on Batam TV clearly. . From the results of analysis and calculations using the EPIC Model parameters with an EPIC RATE percentage of 4.46 it is found that this promotional video is effective and feasible to be published and distributed to Batam Tv consumers.